(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
three groups of composites were fabricated: glass/epoxy composites A, B,C,D,E and F which contains 0, 10, 20, 30, 40 and 50 wt. % glassfibre reinforcement respectively. Naonclay/epoxy composite B, C, D, E and F, with 0, 1, 2, 3, 4 and 5 wt.% nanoclay content respectively. Hybrid composites B, C,D, and F, contain equal amount of epoxy ( 60 wt. %), 39, 38, 37, 36, and 35 wt. % glassfibre and 1, 2, 3, 4, and 5 wt. % nanoclay content respectively. Sample A is the Control sample with 100 wt. % epoxy. Tensile properties of S-glassfibre/nanoclay/epoxy hybird nanocomposite E, which contains 60 wt. % epoxy, 4 wt & nanoclay and 36 wt. % glassfibre was found to be the overall best performing composite in the mechanical properties.